Analisis Implementasi Hukum dan Nilai Pancasila dalam Perlindungan Hak Asasi Yang Dimiliki Oleh Manusia - Faturohman Faturohman; Silvia amanah; Zakia AriKinanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Implementation of the principles of the rule of law and Pancasila democracy in the context of protecting the rights of every human being in Indonesia. The values associated with Pancasila, in protecting one's rights, are very diverse. The first value of Pancasila, if it is related to the rights that every human being has, means affirming recognition of God the Creator. The second value is that humans have equal dignity and rights that must be respected by each other. The values of Pancasila must be put forward in order to unite the Indonesian nation, so that the Indonesian state becomes one united nation. The fourth principle, if related to the rights possessed by humans, emphasizes the importance of fair distribution of resources and opportunities, as well as being able to overcome all forms of injustice in society. Finally, the fifth principle is related to the rights possessed by every human being, meaning that the value of Pancasila places greater emphasis on the importance of democratic governance, by providing space for participation for citizens to be active in society.